2020
DOI: 10.3390/polym12020447
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Polymer Melts Crystallize via Structurally Polydisperse Nanoscale Clusters: Insights from Polyethylene

Abstract: This study demonstrates that monodisperse entangled polymer melts crystallize via the formation of nanoscale nascent polymer crystals (i.e., nuclei) that exhibit substantial variability in terms of their constituent crystalline polymer chain segments (stems). More specifically, large-scale coarse-grain molecular simulations are used to quantify the evolution of stem length distributions and their properties during the formation of polymer nuclei in supercooled prototypical polyethylene melts. Stems can adopt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…In turn, we were able to represent an individual n -C 720 H 1442 chain using 240 SDK beads, substantially reducing the number of interaction sites required to simulate polyethylene crystallization in each of the 400-chain systems (96,000 coarse-grain sites vs over 850,000 atomic sites) and enabling us to undertake the current study. We have previously established that the SDK model is suitable for investigating polyethylene systems and processes in silico (see ref ) and have leveraged the SDK model to study various facets of crystal nucleation in entangled polyethylene melts. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, we were able to represent an individual n -C 720 H 1442 chain using 240 SDK beads, substantially reducing the number of interaction sites required to simulate polyethylene crystallization in each of the 400-chain systems (96,000 coarse-grain sites vs over 850,000 atomic sites) and enabling us to undertake the current study. We have previously established that the SDK model is suitable for investigating polyethylene systems and processes in silico (see ref ) and have leveraged the SDK model to study various facets of crystal nucleation in entangled polyethylene melts. , …”
Section: Methodsmentioning
confidence: 99%
“…While there has been, and continues to be, much experimental work on polymer crystal nucleation as well as theoretical work on nucleation processes, simulations are being increasingly leveraged to provide direct, unambiguous access to sub-nano spatiotemporal resolutions, namely, the time and length scales relevant to polymer crystal nucleation. For more than two decades, simulations have been used to study the molecular-level details of polymer crystal nucleation under nonflow conditions in both solutions and melts. In recent years, several groups have also started using molecular simulations to study polymer crystal nucleation in the presence of shear and extension ,,, conditions, emulating flow-induced nucleation. Other groups have leveraged molecular simulations to characterize how polymer crystal nucleation is affected at the molecular level by molecular weight distributions, additives, , interfaces, and changes in the polymer architecture ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The material structural elements can vary significantly in scale, ranging from atomic-scale lattices to bridge-sized truss structures. SMs are typically studied at four different structural scales, namely, the sub-microstructure, the microstructure, the mesostructure and the macrostructure (Figure 1) (Zhao et al , 2019; Liu et al , 2018; Hall et al , 2020; Borgue et al , 2019; Barrios-Muriel et al , 2020; Yeh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in silico work has probed polymer crystal nucleation in the context of isolated chains, 41,65,69 solutions, 49,62,63,69 and melts. 33,[35][36][37][38][39][40]52,53,55,57,60,64 Simulations have also been used to elucidate the effects of molecular weight distribution, 28,[31][32][33]44 chain topology (e.g., linear vs. ring chains), 30 chain branching, 33,34,40 and cross-linking 70 on polymer crystal nucleation. There has been much interest in the evolution of chain conformations, 32,33,39,53,60,61,69 topological details related to chain folding, 28,29,32,33,[37][38][39]49,57,64,71 and connect...…”
Section: Introductionmentioning
confidence: 99%
“…33,[35][36][37][38][39][40]52,53,55,57,60,64 Simulations have also been used to elucidate the effects of molecular weight distribution, 28,[31][32][33]44 chain topology (e.g., linear vs. ring chains), 30 chain branching, 33,34,40 and cross-linking 70 on polymer crystal nucleation. There has been much interest in the evolution of chain conformations, 32,33,39,53,60,61,69 topological details related to chain folding, 28,29,32,33,[37][38][39]49,57,64,71 and connecting entanglements/disentanglement to observed crystallization phenomenology. 48,49,54,72 For example, Luo and Sommer 54 demonstrated that local entanglements play a key role in polymer crystallization memory effects, and revealed connections between local entanglement lengths, stem lengths and densities.…”
Section: Introductionmentioning
confidence: 99%